A Laboratory-Based Study of the Priming Effects of Food Cues and Stress on Hunger and Food Intake in Individuals with Obesity - Chao, Ariana M. (Obesity (Silver Spring), 2020)
OBJECTIVE: To assess the effects of exposures to food cues and stress on hunger and food intake and examine whether cue responses differ by weight status. METHODS: In a laboratory-based, experimental study, participants (N=138) were exposed to stress, neutral, and food cues delivered using an individualized script-driven imagery task on three days. After each cue exposure, participants ate high- and low-calorie snack foods ad-libitum (Food Snack Test; FST). Hunger was measured by visual analog scales. RESULTS: Food cues elicited significantly greater increases in hunger compared to neutral and stress stimuli. Cue-induced hunger did not differ by weight status. Participants consumed a similar number of total calories across stimuli. In response to food cue provocation, participants with obesity consumed 81.0±4.0% of calories from high-calorie foods, which was significantly greater than participants with normal weight (63.5±3.6%; p=0.001). After the stress cue, participants with obesity consumed 81.4±4.0% of calories from high-calorie foods which was significantly more than participants of normal weight (70.2±3.6%; p=0.04). Energy intake from high-calorie foods did not differ by weight status after the neutral cue. CONCLUSIONS: Among individuals with obesity, exposure to food and stress cues shifted consumption to high-calorie snack foods within a well-controlled experimental setting.